Cow-side milk progesterone testing - Edward P. Call; Jeffrey S. Stevenson (Kansas Agricultural Experiment Station Research Reports, 1987)
Cow-side milk progesterone tests are effective in determining the presence of an active corpus luteum (CL) on the ovary. The test is best used as an adjunct to the Preventive Herd Health Program (PHHP) as a means of identifying cows that have not yet been detected in heat and are candidates for synchronization with prostaglandin (PGF). Several test kits are on the market, and all involve similar chemical principles. However, each test has its own protocol, so read and follow directions EXACTLY. A "control" or "sample" must be run with each test for comparison.; Dairy Day, 1987, Kansas State University, Manhattan, KS, 1987.
Keywords: Kansas Agricultural Experiment Station contribution; no. 88-114-S; Report of progress (Kansas Agricultural Experiment Station); 527; Dairy; Progesterone; Corpus luteum; Prostaglandin F2-α; Estrous cycle; Milk